ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WAKTU PROSES PENGELUARAN BARANG RETUR DENGAN METODE FISHBONE DI GUDANG TRANSMART BUAHBATU BANDUNG - Muhammad Adhya Fadillah; Nurillah Jamil Achmawati Novel; Bambang Irawan (Jurnal Bisnis dan Kewirausahaan, 2023)
This research was conducted with the purpose of analyzing the factors that influence the process of returning goods from the Transmart Buahbatu Bandung warehouse, in order to ensure smooth and efficient return processes. Therefore, this analysis can be used as an evaluation material during the return goods process. This study was conducted in the receiving division of Transmart Buahbatu Bandung, using a qualitative research approach, namely the fishbone analysis method, and employing data collection techniques such as observation, interviews, and documentation. The results of this study revealed that there are three factors that significantly affect the time it takes to process the return of goods from the warehouse, namely a shortage of human resources, disorganized storage, and inadequate facilities